(untitled) (Research, Society and Development, 2025)
Objective: To present a scope review protocol to identify and organize the available evidence on the equivalence between the measurement of glomerular filtration rate and the CKD-EPI formula for its estimation. Methods: This is a scope review protocol developed according to PRISMA-P guidelines for reporting review protocols. The search was conducted in the following databases: Lilacs, Scielo, Pubmed, Cochrane Library, and CAPES journals. Twelve independent reviewers screened the articles by title and abstract. Subsequently, the full text of the included articles was read, considering the eligibility criteria. Results and Discussion: Renal function is often assessed through formulas based on serum creatinine, such as the CKD-EPI and MDRD-4 equations, due to the difficulty and cost of direct measurements like inulin clearance. The CKD-EPI formula is considered more accurate and was recommended in the 2024 KDIGO guidelines, showing good correlation with creatinine clearance (ClCr), although there is still overestimation of GFR due to creatinine secretion in peritubular capillaries. Studies suggest that CKD-EPI performs better in estimating GFR compared to MDRD-4, especially in the early stages of chronic kidney disease (CKD), but in advanced stages, MDRD-4 may be more appropriate. The CKD-EPI formula has also been validated in different populations, including the Korean population, demonstrating its global applicability. The use of these equations is crucial for CKD stratification, influencing therapeutic approaches and preventing complications, highlighting the importance of studies evaluating the accuracy of these formulas in estimating GFR. Conclusion: In this regard, this scope review protocol presents the current landscape of research on the topic, identifying existing gaps in the evidence base.